Correlation Beetwen Body Mass Index, Macro Nutrition Intake (Energy, Protein, Fat, Carb) with Vo2Max Value on Employees of Aisyah Pringsewu University in 2021 - Muharramah, Alifiyanti; Komala, Ramadhana; Dewi, Afiska Prima; Wati, Desti Ambar; Febriani, Wiwi (Universitas Aisyah Pringsewu, 2022)
Fitness and health are important aspects that must be owned by a person. One of the things is cardiovascular fitness (cardiorespiratory) because it is known to affect individual fitness levels for a person, for fitness measurements it can be expressed by maximum oxygen volume (VO2max). One of the factors that cause heart disease is low cardiorespiratory fitness. The purpose of this study was to determine the relationship between body mass index, macronutrient intake and the VO2max value of Aisyah Pringsewu University Employees in 2021. The design of this study used a cross-sectional. The number of research samples was 78 consisting of 30 men and 48 women with an average age of 30.81 ± 6.58 years. Fitness was measured using the 20-Meters Shuttle Run Test. The results of statistical analysis showed that there was a significant relationship between body mass index and VO2max value (p less than 0.05), and there was no relationship between macronutrient intake and VO2max value (p less than 0.05). In conclusion, body mass index has a significant relationship with the vo2max value in employees. However, there was no significant relationship between macronutrient intake. Abstrack: Kebugaran dan kesehatan adalah aspek penting yang harus dimiliki oleh seseorang. Salah satu hal yaitu kebugaran jantung paru (kardiorespirasi) karena diketahui dapat mempengaruhi tingkat kebugaran individu bagi seseorang, untuk pengukuran kebugaran dapat dinyatakan dengan volume oksigen maksimal (VO2max). Salah satu faktor penyebab terjadinya penyakit jantung yaitu rendahnya kebugaran kardiorespiratori. Tujuan penelitian ini adalah untuk mengetetahui hubungan indeks massa tubuh, asupan zat gizi makro dengan dengan nilai VO2max pada Karyawan Universitas Aisyah Pringsewu Tahun 2021. Desain penelitian ini menggunakan Cross Sectional. Jumlah sampel penelitian sebesar 78 yang terdiri dari 30 laki laki dan 48 perempuan dengan usia rata rata 30,81 ± 6,58 tahun. Kebugaran diukur menggunakan 20-Meters Shuttle Run Test. Hasil analisis statistik menunjukkan terdapat hubungan yang signifikan antara indeks massa tubuh dengan nilai VO2max (p kurang dari 0,05), serta tidak ada hubungan antara, asupan zat gizi makro dengan nilai VO2max (p kurang dari 0,05). Kesimpulannya indeks massa tubuh memiliki hubungan yang bermakna dengan nilai vo2max pada karyawan. Tetapi, asupan zat gizi makro tidak terdapat hubungan yang signifikan.